2012
DOI: 10.1159/000338125
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology in the Etiopathogenesis of Pouchitis

Abstract: <b><i>Background:</i></b> Pouchitis is the most common long-term complication in ulcerative colitis that follows restorative proctocolectomy. Clinical evidence suggests that dysbiosis plays a key role in its pathogenesis. <b><i>Methods:</i></b> Current literature on the topic was reviewed. A therapeutic approach was proposed based on the literature along with personal experience from the subspecialty Pouchitis Clinic. <b><i>Results:</i></b>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…The relatively short time from ileoanal pouch formation to inflammation allows the convenient longitudinal study of the microbiota which gives insight into potential patterns occurring both in disease and nondiseased states. Interestingly, inflammation within the ileoanal pouch is rarely seen in patients who have the same operation for familial adenomatous polyposis (FAP), thus raising the possibility that pouchitis shares a similar pathogenesis to the inflammation that is seen in UC …”
Section: Introductionmentioning
confidence: 99%
“…The relatively short time from ileoanal pouch formation to inflammation allows the convenient longitudinal study of the microbiota which gives insight into potential patterns occurring both in disease and nondiseased states. Interestingly, inflammation within the ileoanal pouch is rarely seen in patients who have the same operation for familial adenomatous polyposis (FAP), thus raising the possibility that pouchitis shares a similar pathogenesis to the inflammation that is seen in UC …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to UC, pouchitis is rarely seen in patients with familial adenomatous polyposis with IPAA. This suggests that similar factors as those playing a role in the pathogenesis of UC may also be involved in the onset and perpetuation of pouchitis 3. In most patients, there is probably an abnormal immune response against the commensal microbiota and only a minority develop pouchitis secondary to Clostridium difficile or cytomegalovirus infection, non-steroidal anti-inflammatory drug use or ischaemia 4.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, no exact bacterial species, which might be closely associated with the development of IBD, have been described. The main explanation could be, that only approximately 50% of intestinal bacteria are culturable [ 18 ]. Kotlowski et al combined in their study culture-independent methods with bacterial culture and found out, that the tissue of IBD patients contained 3–4 logs higher amounts of bacteria from Enterobacteriaceae family and the difference between IBD patients and the controls was statistically significant.…”
Section: Discussionmentioning
confidence: 99%